Analyzing the dynamics behind ethical banking practices using fuzzy cognitive mapping - Azevedo, A.; Ferreira, F. (Operational Research, 2019)
Because the perceived ethics of a banking institution can affect its reputation, concern over ethical practices in the banking sector is rapidly increasing. The alignment of such practices with daily operations, however, requires dealing with a wide range of variables, tangible or intangible, and constitutes a notoriously difficult endeavor. Still, due to the rapidly changing economic environment and current sharp competition in the banking industry, a better understanding of this alignment can help bank managers and other key players enhance value creation through more informed decisions, contributing to stronger integration of ethical practices in the banks’ daily activities. This paper proposes the use of fuzzy cognitive maps (FCMs) to analyze the dynamics behind ethical banking practices. Grounded on intensive group meetings with a panel of senior executives from the banking industry, the result is a well-informed process-oriented framework that sheds light on the manner in which ethical practices interrelate with each other. Implications, advantages and shortcomings of our proposal are also discussed.